BISHOP OF PODLASIE, ARCHBISHOP JAN MARCELI GUTKOWSKI DEFENDER OF THE FAITH AGAINST TSARISM - BYLINA, Sławomir (HUMANITARIAN STUDIES: HISTORY AND PEDAGOGY, 2021)
Annotation. The profile of the bishop of the diocese of Janów or Podlasie, Jan Marcel Gutkowski, who was in southern Podlasie in the years 1826-1840 during the period of the Kingdom of Poland, has a unique dimension of the symbolic fight against tsarism. A special figure recognized during his ministry as a «pillar of the Polish Church» clashed with the restrictions on professing the Catholic faith in the area to which Tsarist Russia claimed rights. During his priestly ministry, Jan Marceli Gutkowski was a military chaplain and even the chief chaplain of the Polish Army during the period of the Duchy of Warsaw until 1925. In his episcopal ministry, he strived for a proper understanding of the sacrament of marriage, defended the proclamation of the Word of God in the Kingdom of Poland, also by priests of the Greek-Catholic denomination. Such an attitude of a courageous priest contributed to difficulties on the part of tsarist officials, who from the level of the county and province hindered the proper functioning of the diocese. As a result of complaints to the Vatican, Bishop Gutkowski was expelled from the diocese by the tsarist authorities and sent to Ozieran. After the decision of Pope Gregory XVI, he was appointed titular archbishop of Marcianopolitan and sent his fate to Lviv in Ukraine, where he was buried in the Lychakiv cemetery. It can be said that this is an interesting figure also for today's times.